Weakly acidic pH reduces inflammatory cytokine expression in airway epithelial cells. Issue 1 (December 2016) - Hackett, A.; Trinick, R.; Rose, K.; Flanagan, B.; McNamara, P.
Abstract Background Aspiration lung disease (ALD) is a common cause of respiratory morbidity in children and adults with severe neurodisability (sND). Recent studies suggest that chronic microaspiration of gastric contents is associated with mild rather than low, airway acidification. We investigated inflammatory responses to infection by airway epithelial cells (AECs) exposed to weakly acidic media. Methods Using pH measurements from children with sND at high risk of ALD as a guide, we incubated AECs in weakly acidic (pH5.5–7.4) media alone; in combination with lipopolysaccharide (LPS); or prior to LPS stimulation at normal pH. Interleukin (IL) -6 and IL-8 expression were measured. Results IL-6/8 expression in AECs simultaneously exposed to weakly acidic media and LPS for 4 h was reduced with no effect on cell viability. Pre-incubation of AECs at weakly acidic pH also reduced subsequent LPS-induced cytokine expression. Suppression of inflammation was greatest at lower pHs (pH 5.5–6.0) for prolonged periods (16/24 h), but this also adversely affected cell viability. Conclusion AEC inflammatory responses to bacterial stimuli is markedly reduced in a mildly acidic environment.